Ovarian stromal tumor with minor sex-cord element with virilizing menifestations: a rare case report - Sharma, Reena; Vij, Anju; Mahajan, Neelam; Chaudhary, Usha Kumari; Sharma, Ajay; Kumar, Arvind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sex cord stromal tumor is a rare variety of ovarian tumor. These tumor have association with testosterone production which lead to virilisation in females. Here we report a case of 40yrs old female P2 L2 who presented with clinical signs and symptoms of virilisation: deepening of voice, hirsutism (Ferriman Gallwey score24), clitoromegaly, and breast atrophy. In this patient, serum testosterone and TSH levels were raised. An ovarian mass was detected on ultrasonography. Exploratory laparotomy proceeds, total abdominal hysterectomy with bilateral salpingo-opherectomy was done. On histopathological examination the ovarian mass turned out a sex-cord stromal tumor of fibroma thecoma group-cellular fibroma with minor sex-cord like elements. Post-operatively her serum testosterone level declined and signs and symptoms of virilisation started regressing.